2010
DOI: 10.1007/s10029-010-0687-7
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic repair of potentially contaminated abdominal ventral hernias using a xenograft: a case series

Abstract: Strattice™ Reconstructive Tissue Matrix appears to be a promising new biological matrix for laparoscopic ventral hernia repair, especially in potentially contaminated fields. Further studies and long-term follow-up are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…5,[8][9][10]23,29,30 On the basis of the reported success of these groups and our own experience with biologic materials in contaminated fields, it does seem to be safe in clean-contaminated and contaminated fields. As we noted an overall wound complication rate of 48%, no patients required complete mesh excision, developed chronic draining sinuses, or mesh infections.…”
Section: Discussionmentioning
confidence: 93%
“…5,[8][9][10]23,29,30 On the basis of the reported success of these groups and our own experience with biologic materials in contaminated fields, it does seem to be safe in clean-contaminated and contaminated fields. As we noted an overall wound complication rate of 48%, no patients required complete mesh excision, developed chronic draining sinuses, or mesh infections.…”
Section: Discussionmentioning
confidence: 93%
“…The immediate mesh repair is deferred only in the presence of abundant peritoneal contamination [87,[91][92][93][94]. The biologic meshes may provide a new prospect in a contaminated surgical field [95], also in laparoscopic emergency hernia repair, with good results in terms of recurrence and wound infection [96,97].…”
Section: Acute Presentation: Emergencymentioning
confidence: 99%
“…They identified 4 recurrences (7.2 %) at a mean follow-up of 30.6 months, but noted that all recurrences were within 3 weeks of the repair and all were in patients that were bridged. There have been three reports on the use of Strattice for ventral hernia repair and one case series of three patients [2225]. Rosen et al [22] reported on a small group of 12 patients with combined ventral and parastomal hernias repaired with a retrorectus technique using Strattice mesh.…”
Section: Discussionmentioning
confidence: 99%